Understanding the Complexities of Educational Change Resistance amongst Academic Staffs - Lasisi, Adekola Kamil; Oreagba, Fatimah; Abdulkareem, Habibat Bolanle (Indonesian Journal of Educational Research and Review, 2024)
The resistance change in the educational system has been observed among school curriculum as a result of change of government. The research aimed to delve into the intricacies of resistance to educational change among primary school academic staffs. Qualitative approach design was adopted. Convenient sampling technique was used to select ten participants through utilizing an online survey interview method. The tool utilized for this investigation was the Educational Change Resistance Interview (ECRI). Thematic qualitative design was used to analyses the data collected. Analysis of the gathered data led to the identification of recurring themes. The findings underscored the nuanced and multifaceted nature of educational change, emphasizing the need for a comprehensive and context-specific comprehension of academic staffs' viewpoints, experiences, and the various influencing factors impacting their resistance or acceptance of change. Moreover, the study highlighted potential strategies to mitigate resistance to educational change, including aspects such as compensation, motivation, support and training, as well as effective communication and involvement strategies. In conclusion, this research offers valuable insights into the challenges and opportunities associated with educational change in primary schools, laying the groundwork for future efforts to foster a culture of resilience, collaboration, and innovation within the educational sector.